Ensino fundamental de nove anos: sentimentos revelados por professores do primeiro ano - Jarussi, Margarete Borsi (2013)
Since educational laws 11.11405 and 11.274 elementary education has now a nine year length and the admission of first year students at the age of six, respectively. Educational chances have direct implications on school routine, especially on first year teacher interaction. The present research aim to indentify and comprise first year teacher feelings and emotions in the nine year elementary education. Prioritizing affective dimensions, the theoretical reference adopted is Henri Wallon´s theory of development. The research was made at a state school in the São Paulo metropolitan region. The methodological approach is qualitative and, in order to produce data, two first year teachers of the new length elementary education that also taught in the first year of eight year elementary education were interviewed. Whereof interviews, charts and synthesis were elaborated to assist the data discussion. For teachers characterization, a informative questionnaire was set. The results shown teachers feel insecure when it comes to pedagogical practice and first year content, pointing little knowledge on nine year elementary education official documents. Data revealed a further training necessity that engenders teachers affective, cognitive and motor aspects, increasing communication channels, privileging listening and dialogue